(untitled) (Nexo Revista Científica, 2021)
In this paper, a novel hybrid Direct Torque Control (DTC) strategy based on predictive control with optimization of the Proportional-Integral (PI) controller to improve overall performances of Three-Phase Induction Machine (TPIM) drives is proposed. The presented control technique has contained merits of the DTC method such as fast dynamic response, simple structure, less dependence to machine parameters and merits of vector control method such as high accuracy. Furthermore, a hybrid DTC method with optimal voltage vectors is presented. In the proposed control system, Genetic Algorithm (GA) is employed to obtain optimal values of the PI controller parameters. Finally, simulation results under the presented control strategy showed good performances of this method in comparison with DTC and vector control techniques.